Value of preoperative evaluation of FEV1 in patients with destroyed lung undergoing pneumonectomy - a 20-year real-world study - Wenbo Li; Jing Zhao; Changfan Gong; Ran Zhou; Dongjie Yan; Hongyun Ruan; Fangchao Liu (BMC Pulmonary Medicine, 2024)
Abstract Background Clinical guidelines recommend a preoperative forced expiratory volume in one second (FEV1) of > 2 L as an indication for left or right pneumonectomy. This study compares the safety and long-term prognosis of pneumonectomy for destroyed lung (DL) patients with FEV1 ≤ 2 L or > 2 L. Methods A total of 123 DL patients who underwent pneumonectomy between November 2002 and February 2023 at the Department of Thoracic Surgery, Beijing Chest Hospital were included. Patients were sorted into two groups: the FEV1 > 2 L group (n = 30) or the FEV1 ≤ 2 L group (n = 96). Clinical characteristics and rates of mortality, complications within 30 days after surgery, long-term mortality, occurrence of residual lung infection/tuberculosis (TB), bronchopleural fistula/empyema, readmission by last follow-up visit, and modified Medical Research Council (mMRC) dyspnea scores were compared between groups. Results A total of 96.7% (119/123) of patients were successfully discharged, with 75.6% (93/123) in the FEV1 ≤ 2 L group. As compared to the FEV1 > 2 L group, the FEV1 ≤ 2 L group exhibited significantly lower proportions of males, patients with smoking histories, patients with lung cavities as revealed by chest imaging findings, and patients with lower forced vital capacity as a percentage of predicted values (FVC%pred) (P values of 0.001, 0.027, and 0.023, 0.003, respectively). No significant intergroup differences were observed in rates of mortality within 30 days after surgery, incidence of postoperative complications, long-term mortality, occurrence of residual lung infection/TB, bronchopleural fistula/empyema, mMRC ≥ 1 at the last follow-up visit, and postoperative readmission (P > 0.05). Conclusions As most DL patients planning to undergo left/right pneumonectomy have a preoperative FEV1 ≤ 2 L, the procedure is generally safe with favourable short- and long-term prognoses for these patients. Consequently, the results of this study suggest that DL patient preoperative FEV1 > 2 L should not be utilised as an exclusion criterion for pneumonectomy.